REAKTUALISASI NILAI AL-QUR'AN DALAM KONTEKS KEARIFAN LOKAL: PERAN DOSEN MEMBANGUN KEILMUAN ISLAM YANG PROFESIONAL DAN BERAKHLAK MULIA - Jamaluddin Thaib (Hijri, 2025)
The reactualization of Qur'anic values within the context of local wisdom is an important effort to present Islamic teachings in a contextual, relevant, and solution-oriented manner in society. In higher education, lecturers hold a strategic position as key actors in transforming Islamic values into scientific development, character building, and social practices rooted in local culture without losing the substance of the revealed teachings. This article aims to analyze the relationship between the universal values of the Qur'an and local wisdom and to explain the role of lecturers in developing professional and noble Islamic scholarship. The method used is a literature study with a descriptive-analytical approach. The results of the study indicate that Qur'anic values such as justice, honesty, trustworthiness, deliberation, moderation, and respect for human dignity have common ground with many local traditions that exist within society. Lecturers play a role as agents of value integration, developers of Islamic academic culture, researchers responsive to social realities, and moral role models in building scientific professionalism. Thus, the reactualization of Qur'anic values based on local wisdom not only strengthens an inclusive Islamic identity, but also produces a model of Islamic higher education that is oriented towards academic excellence and the formation of noble morals.